Evaluation of the efficacy and safety of cow placenta extract lotion versus minoxidil 2% in the treatment of female pattern androgenetic alopecia - Tara Barat, MD; Fahimeh Abdollahimajd, MD; Sahar Dadkhahfar, MD; Hamideh Moravvej, MD (International Journal of Women's Dermatology, 2020)
Background: Placenta extract has been shown to improve androgenetic alopecia (AGA) by inducing the anagen phase and increasing hair follicle density and size. Objective: This study aimed to evaluate the safety and efficacy of cow placenta extract lotion compared with topical minoxidil 2% as a gold standard treatment for female pattern AGA. Methods: In this double-blind, randomized controlled trial, a total of 90 women with AGA were enrolled and randomly assigned to receive either topical minoxidil 2% or cow placenta solutions. At the end of the sixth month, the number of hair follicles was evaluated using a trichoscope and compared with the baseline. Global photographic review was also conducted by a blinded dermatologist. Results: By the end of the sixth month, there was an increase in total hair count in the specified area in both groups. The mean increase in hair count was 10.9 ± 5.74 and 10.2 ± 6.5 for minoxidil and cow placenta groups, respectively (p = .63). The percentage of patients who were rated as having moderate or marked growth was 44.2% and 32.2% in the cow placenta and minoxidil groups, respectively (p = .90). Limitations: The study limitations were the limited number of cases, short duration of treatment, and the fact that none of our participants volunteered to undergo a biopsy to evaluate microscopic changes. Conclusions: Cow placenta hair-tonic lotion can be as effective as minoxidil 2% for female pattern AGA.